Eliciting Circular Economy Performance Via Zero Waste Practices, Supply Chain Collaboration, and Circular Economy Entrepreneurship: A Network Theory Perspective. - Rijal, Anita (Nepalese Journal of Management Science and Research, 2025)
Discovering ways to achieve greater circular economy (CE) performance from the lenses of small and medium-sized (SMEs) has been of crucial interest to scholars and policymakers due to its ability to curb the limitations of the linear economy and preserve natural resources. Extant literature insinuates that SMEs due to their many constraints form supply chain collaborations (SCC) to amass resources in their effort to promote CE performance. However, a research gap exists regarding how SMEs' efforts to adopt zero waste practices (ZWP) drive the formation of circular-oriented SCC which in turn initiates the development of circular economy entrepreneurship (CEE) for enhanced CE performance. Thus, this study draws on the network theory to explore the framework through which the adoption of ZWP impacts SCC, CEE, and CE performance. Based on quantitative analysis of responses from 152 managers of SMEs in Nepal, the results reveal that ZWP positively and significantly drives SCC and CE performance. Interestingly, the findings discover that SMEs in SCC significantly develop CEE which also robustly advance CE performance. The serial indirect effects reveal that SCC and CEE have mediating influences in the relationship between ZWP and CE performance.This study extends the ZWP discussion to the CE domain, thereby identifying ZWP as a potent means for managers to drive SCC, CEE and CE performance. This study presents future research directions as well as guidance for managers, policymakers, and scholars.